A new approach to the modeling of network traffic in simulations - Fras, Matjaž (Informacije MIDEM, 2009)
Simulations of telecommunications networks have become very important tools for their evaluation. A very important influence in simulations has network traffic. This paper introduces new concepts for the modeling of measured network traffic in simulation tools. With these new concepts, we can improve descriptions of the random packet-size process, especially for maximal-packets of network traffic, which have a very great impact on the bit or packet rates of network traffic. The suggested methods improve the contents of packets, especially maximal packets in modeled network traffic simulations, which leads to smaller differences in bit and packet-rates between measured and modeled network traffics.
Keywords: komunikacijska omrežja; modeliranje; omrežni promet; paketna omrežja; Pareto porazdelitev; simulacije